Regulating the lncRNA DSCR9/RPLP2/PI3K/AKT axis: an important mechanism of Xinfeng capsules in improving rheumatoid arthritis - Wang, Fanfan; Liu, Jian (Frontiers in Immunology, 2024)
Background: Rheumatoid arthritis (RA) is a systemic autoimmune disease characterized by chronic and symmetrical polyarthritis. RA patients often experience inflammatory reactions and hypercoagulable states, which together affect the self-perception of patient (SPP). Currently, inhibiting inflammation and hypercoagulable states are common treatment methods for alleviating RA symptoms. Xinfeng Capsule (XFC) has a long history of treating RA, and can effectively improve the inflammatory response and hypercoagulable state of RA. However, the potential mechanisms have not yet been determined. Purpose and study design: This study elucidated the action mechanism of XFC in RA inflammation and hypercoagulability through the lncDSCR9/RPLP2/PI3K/AKT axis. Results: Clinical observations indicated that there was a strong link between XFC therapy and improvements in inflammatory and coagulation biomarkers, as well as SPP among RA patients. The subsequent network pharmacology analysis results identified the PI3K/AKT signaling pathway as a potential mediator for XFC treatment of RA. Furthermore, clinical validation and sequencing results revealed that lncRNA DSCR9 expression (a gene implicated in inflammation and coagulation) was negatively correlated with clinical markers of inflammation and coagulation, while positively correlated with SF-36 indicators. Notably, XFC treatment remarkably upregulated lncRNA DSCR9 expression and downregulated PI3K and AKT expressions, showing opposite expression trends to the untreated cases. The regulatory effect of XFC on the lncRNA DSCR9/RPLP2/PI3K/AKT axis in RA was investigated using techniques such as RNA pull-down assay, Western blot analysis, RT-PCR, and EdU assay. Moreover, the administration of the PI3K/AKT agonist RMH can counteract the effects of XFC on p-PI3K, p-AKT, inflammation, and hypercoagulability, reinforcing the role of the PI3K/AKT pathway. Finally, animal studies utilizing HE staining and transmission electron microscopy (TEM) demonstrated that XFC notably decreased PI3K and AKT expressions in adjuvant-induced arthritis (AA) rats, mitigated inflammation and hypercoagulability, and enhanced the ultrastructure of synovial cells. These findings underscored the potential mechanisms of XFC in the treatment of RA. Conclusion: Regulating the lncRNA DSCR9/RPLP2/PI3K/AKT axis may be an important mechanism by which XFC improved RA inflammatory response and hypercoagulable state.